Progression of obesity and abdominal obesity after the COVID-19 pandemic in Colombia: a comparison of two cross-sectional population-based studies - Carlos O Mendivil; Valentina Cuellar-Rodríguez; Agustín Pérez-Londoño; Valentina Guatibonza-García; Carolina Betancourt-Villamizar (BMJ Public Health)
Introduction We explored the changes in the prevalence and distribution of excess body adiposity in urban Colombia after the COVID-19 pandemic and associated lockdown.Methods We executed a population-based, stratified, multi-stage study of individuals aged 2–80 years from five Colombian cities, between November and December 2022. We explored the prevalences of excess adiposity measures and their association with socioeconomic variables and contrasted the results with the previous wave of the study, conducted in 2018.Results We studied 2115 individuals (83.5% adults, 51.7% female). Between 2018 and 2022, the adult prevalence of excess body weight (EBW, body mass index >25 kg/m2) increased by 4.5% in males and decreased by 0.6% in females. Women had almost twice the prevalence of obesity as men. The prevalence of obesity for underage females soared from 7.6% in 2018 to 18.4% in 2022. Abdominal obesity increased by 10.3% in men, up to 39.8%. Adult female obesity was negatively associated with socioeconomic status (SES) (OR 2.01 (95% CI 1.33 to 3.04) for lowest SES relative to highest). Abdominal obesity among women in the lowest SES reached 55.2% in 2022. There was a strong negative relationship between education and EBW among women, the OR of obesity for women with only primary education relative to college graduates was 2.48 (95% CI 1.52 to 4.06).Conclusions The obesity epidemic worsened in urban Colombia after the COVID-19 pandemic and associated lockdown, especially among adult males and underage females. The burden of excess adiposity is concentrated in women from disadvantaged groups.